2022
DOI: 10.5194/amt-2022-71
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of OCO-2 target observations to MUCCnet – Is it possible to capture urban XCO2 gradients from space?

Abstract: Abstract. In this paper, we compare Orbiting Carbon Observatory 2 (OCO-2)’s measurements of column-averaged dry air mole fractions of CO2 (XCO2) and its urban-rural differences against ground-based remote sensing data measured by the Munich Urban Carbon Column network (MUCCnet). Since April 2020, OCO-2 regularly conducts target observations in Munich, Germany. Its target mode data provides high resolution XCO2 within a 15 km×20 km target field-of-view, that is greatly suited for carbon emission studies from sp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…OCO-3 has recorded more than OCO-2 Target mode is primarily used for validation purposes, with many targets located at Total Column Carbon Observing Network (TCCON; Wunch et al, 2011) sites, but it also includes targets over certain megacities and some point sources, such as volcanoes and large power plants. OCO-3's Target mode is utilized similarly, but has a larger spatial coverage which can also be used to study the carbon cycle on local scales (Kiel et al, 2021;Rißmann et al, 2022). Studies using OCO-2 Target data have shown the instrument's ability to detect anthropogenic X CO2 enhancements on subcontinental scales (Hakkarainen et al, 2016), from megacities (Schwandner et al, 2017), and from industrial sources such as iron and steel plants (Wang et al, 2018).…”
Section: Oco Target and Sam Mode Measurementsmentioning
confidence: 99%
“…OCO-3 has recorded more than OCO-2 Target mode is primarily used for validation purposes, with many targets located at Total Column Carbon Observing Network (TCCON; Wunch et al, 2011) sites, but it also includes targets over certain megacities and some point sources, such as volcanoes and large power plants. OCO-3's Target mode is utilized similarly, but has a larger spatial coverage which can also be used to study the carbon cycle on local scales (Kiel et al, 2021;Rißmann et al, 2022). Studies using OCO-2 Target data have shown the instrument's ability to detect anthropogenic X CO2 enhancements on subcontinental scales (Hakkarainen et al, 2016), from megacities (Schwandner et al, 2017), and from industrial sources such as iron and steel plants (Wang et al, 2018).…”
Section: Oco Target and Sam Mode Measurementsmentioning
confidence: 99%